Electronic Means of Communication as a Means of Remote Speech Therapy for Adult Stroke Survivors - Ovcharenko, Maryna (Educological discourse, 2023)
The article discusses the types of strokes, general statistics and prevalence of strokes in the world and in Ukraine. The survey and tendencies to occurrence in younger people were carried out; the factors of stroke occurrence in young people have been studied. Statistics on the uneven distribution of strokes by gender were analyzed. It has been determined that women are at higher risk of suffering a severe or fatal stroke than men. The main reasons for such statistics are indicated. The main types of speech and language impairments that can occur after cerebral circulatory disorders are analyzed. The leading signs of aphasia, apraxia and dysarthria in adults have been identified. The definition of progressive apraxia of speech is revealed. It is established that these disorders occur due to damage to the language areas of the brain. The advantages of using electronic means of communication in speech-language therapy during quarantine restrictions and martial law in Ukraine are revealed. Software and messengers were characterised, such as Google Meet, Zoom, Teams, and Skype, that are used during distance and/or face-to-face sessions with a speech language pathologist. The main advantages of using these programs and the requirements for a speech language pathologist in the use of electronic means of communication are described. The concept of "social networks" and their impact on the rehabilitation of adult patients is revealed. The positive aspects of using social networks with adults during speech-language therapy, in particular Instagram and Facebook, are highlighted. Mobile applications are described as an additional means of restoring various aspects of speech, language and higher mental functions. It is noted that the current situation in the country, taking into account quarantine restrictions and martial law, can not provide full, continuous and quality speech language therapy in these cases, which leads to the conclusion that the lack of effectiveness of using exclusively traditional methods and techniques to compensate speech and language disorders caused by stroke, and encourages further search for ways to improve it by electronic means of communication. The author sees the need for a research aimed at studying the use of electronic means of communication in speech language therapy for people who have suffered a stroke.